Kompetensi Sumber Daya Manusia Dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Daerah Pada Instansi Pemerintahan Kota Padang - Joni Fernandes; Rilla Yulita (JURNAL PUNDI, 2022)
The purpose of this study was to examine the effect of human resource competence and internal controlsystem on the quality of regional financial reports at padang city government agencies.The population in this study is the finance/accounting  sub-section whice has main tasks that are directly related to the preparation of financial statements at 42 OPD inte environment. Padang city governmain purposive sampling methode hypothesis testing using linier regresion using Software statistical package for the social science version 25 the distributed questionnaire use ordinal scale which is measured throught a likert poin scale 5.the resultsof the study provide evidence that the coefficient value regression variabel human resaurce competence is 0.407 with a tcount value of 5.395 whichis greater than the table valueof 1.97490 so that it can be stated that human resaource competence  has a  positive and significant  effect (0,000 < 0,05) , and the control system the internal variabel regresion  value is 0,329 with  a t-count value value of 4.370 whice is greater  than the t-table value of 1.97490 so it can be stated that the internal control system  has a positive significant effect  (0,000 < 0,05) that it can be councluded that the better the competence human resource and internal control system, that better the results of the financial statements produced.